Rozumna służba a odnowiony umysł w świetle Rz 12,1-2 - Żywica, Zdzisław (Collectanea Theologica, 2018)
Exegetical analysis of propositio 12,1-2 and its rhetorical context allows us to conclude that the overriding message is an encouragement to render “a reasonable service to God”. According to Paul, it relies on the constant and absolute faithfulness of his will to sacrifice “himself” (sōma) in “a living, sacred and pleasant sacrifice”, that is, to the measure of the sinful humanity of mercy in the salvific work of Jesus; “according to the faith received from God” (12,3). For the Apostle, the constantly “renewed mind with the Gospel” and the power of the Holy Spirit is an absolute condition to fully know God’s will, “transform oneself” (sōma) and save it redemptive effectively through God’s “goodness, perfection and love”. It is obvious to him that only a man implanted in Christ through the Gospel, baptism and the Holy Spirit becomes his “image” also in the way of thinking (the mind), therefore he is able to constantly re-explore the sense of “reasonable service” to finally find out that it is “evangelical service” in the power of the Holy Spirit, modeled on Jesus himself. This is the only rationally mature (according to the wisdom and justice of God) and worth of a “new creature” (Christian) the answer to God for the work of salvation made in Christ, who sacrificed himself to God in the Passover as a sacrifice of the “good, perfect, living holy and the kind”.